Regulation of methionine synthesis in Escherichia coli: effect of the MetR protein on the expression of the metE and metR genes. - Maxon, M E (1989)
A plasmid (pRSE562) containing the metE and metR genes of Escherichia coli was used to study the expression of these genes and the role of the MetR protein in regulating metE expression. DNA sequence analysis of the 236-base-pair region separating these genes showed the presence of seven putative met boxes. When this plasmid was used to transform either wild-type E. coli, metE mutant, or metR mutant, MetE enzyme activity increased 5- to 7-fold over wild-type levels. The metR gene was subcloned from pRSE562, and this plasmid, pMRIII, relieved the methionine auxotrophy of a metR mutant after transformation. The metR gene was also cloned into a vector containing the lambda PL promoter, and the MetR protein was overexpressed and purified to near homogeneity. This protein, when added to an in vitro DNA-dependent protein synthesis system in which the MetE and/or MetR proteins were synthesized, caused a large increase in the expression of the metE gene but a decrease in the expression of the metR gene. The in vitro expression of both genes was inhibited by the MetJ protein and S-adenosylmethionine in the presence or absence of MetR protein. These results provide evidence that the product of the metR gene is a trans-activator of the expression of the metE gene and that the expression of the metR gene is under autogenous regulation and is repressed by the MetJ protein.